How does early adulthood arrest alter substance use behavior? Are there differential effects by race/ethnicity and gender? - Hassett-Walker, Connie (J Dev Life Course Criminol, 2017)
PURPOSE: Much criminal justice research has ignored racial/ethnic and gender differences in substance use subsequent to criminal justice involvement. This paper investigated how early adulthood arrest (i.e., 18 to 21 years of age) influences individuals’ subsequent transitions from non-substance use to substance use, and substance use to non-substance use through age 30. We also consider if these relationships differ by race/ethnicity and gender. Processes proscribed by labeling theory subsequent to getting arrested are considered. METHODS: We analyzed 15 waves of data from the National Longitudinal Survey of Youth 1997. Multinomial logistic regressions were performed using Stata software version 14. RESULTS: We found racial/ethnic differences in the effect of arrest on subsequent substance use, particularly marijuana. Being arrested was associated with shifting non-binge drinkers and non-marijuana users into binge drinking and marijuana use; as well as shifting binge drinkers and marijuana users into non-use. This pattern was most evident among White and Black men. For Black men, the association between arrest and both becoming a binge drinker and becoming a non-binge drinker was experienced most strongly during their early twenties. Women’s patterns in substance use transitions following an arrest were less clear than for the men. CONCLUSION: Some results, particularly transitioning into marijuana use, offer qualified support for processes proscribed through labeling theory. Findings that arrest shifts individuals into non-marijuana use suggest that factors not accounted for by labeling theory – arrest serving as a teachable moment for those using substances - may be at play.